Quando o amor é travesti: casamento, amor e afeto para além da heteronormatividade - Miguel, Luiz Henrique (2022)
The general objective of this thesis is to analyze how love relationships and the agency of love are made by observing the life course of 3 transvestites from São Paulo. For this purpose, a qualitative methodology based on the life history technique and in-depth field research was used. Searching for something as subjective as love yielded hours of participation with the three interlocutors in semi-structured interviews that helped to achieve the central objective. As part of the analysis, it is noticed that the categories of romantic love affect all people, flirting with the ideals of heteronormative relationships, however for the transvestites surveyed, this category takes particular formats. Romantic love necessarily involves recognition and leads these subjects to weigh a series of agencies, including their own bodies and the formation of the desired body. As final considerations, it was possible to perceive that love takes different formats, either as a life goal or as a rejection of this goal, in any case it is an important part of the construction of what is or is not success for these transvestites. Public recognition is the realization of romantic love for those who aim for this goal, public displays of affection with a man you love is one of the central pillars that comes into the account when it comes to conquering the ideal partner.